2014
DOI: 10.1186/1471-2334-14-167
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and dengue: a critical and systematic review of quantitative modelling approaches

Abstract: BackgroundMany studies have found associations between climatic conditions and dengue transmission. However, there is a debate about the future impacts of climate change on dengue transmission. This paper reviewed epidemiological evidence on the relationship between climate and dengue with a focus on quantitative methods for assessing the potential impacts of climate change on global dengue transmission.MethodsA literature search was conducted in October 2012, using the electronic databases PubMed, Scopus, Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
224
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(270 citation statements)
references
References 70 publications
7
224
0
14
Order By: Relevance
“…Entre dichos factores sobresalen los cambios climáticos, los ciclos del vector, los serotipos circulantes y las dinámicas poblacionales (10,13,20). De todos ellos, el clima ha sido uno de los factores más estudiados, específicamente los cambios de la temperatura, la precipitación y la humedad, los cuales influyen en los procesos de alimentación, supervivencia y proliferación del vector, así como en la replicación del virus (11,29,30). Los resultados de los estudios hechos en Ecuador sugieren que existe coherencia entre la incidencia del dengue y la temperatura en ciclos bianuales y anuales (13), mientras que en Vietnam se han encontrado asociaciones del dengue con la humedad, la temperatura y la precipitación en modo anual (24).…”
Section: Discussionunclassified
“…Entre dichos factores sobresalen los cambios climáticos, los ciclos del vector, los serotipos circulantes y las dinámicas poblacionales (10,13,20). De todos ellos, el clima ha sido uno de los factores más estudiados, específicamente los cambios de la temperatura, la precipitación y la humedad, los cuales influyen en los procesos de alimentación, supervivencia y proliferación del vector, así como en la replicación del virus (11,29,30). Los resultados de los estudios hechos en Ecuador sugieren que existe coherencia entre la incidencia del dengue y la temperatura en ciclos bianuales y anuales (13), mientras que en Vietnam se han encontrado asociaciones del dengue con la humedad, la temperatura y la precipitación en modo anual (24).…”
Section: Discussionunclassified
“…The climate change can result in a disease incident which is related to environment, including dengue. The climate parameters related to dengue among others are temperature, humidity and rain fall (Naish et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found associations between climatic factors and dengue transmission (see (Naish et al, 2014;Thai and Anders, 2011) for a review). However, modelling approaches and methods to account for climate factors within the model vary considerably, which could lead to differential results regarding the relationships and time lags between climatic factors and dengue relative risk.…”
Section: Introductionmentioning
confidence: 99%